مستوى فاعلية معالجة وسائل الإعلام المحلي للأزمات الداخلية (دراسة ميدانية على القائمين بالاتصال) - المنفي , محمد سالم موسى (Scientific Journal of University of Benghazi, 2022)
The aim of the research is to identify the effectiveness of the local media's handling of its internal crises through the views of communicators in the local press and radio media in the cities of Benghazi and Ajdabiya. This is a descriptive study, based on the descriptive approach to survey studies in the section related to studying communicators. The descriptive approach is a part of survey studies that represents a type of descriptive methodology. The research was applied to 28 communicators in press outlets; 16 communicators from Benghazi News and 12 from Ajdabiya News. This study utilized a survey to collect data. The survey was divided into sections that included all aspects of the research and its objectives. The research was divided into a methodological framework that incorporated the problem of research, its relevance, objectives, questions, the definition of concepts, type of research, methodology, population, methods and data collection tools. The most significant findings of the research included: The results of the research have generally shown that there is little interest on the part of the local media in question in addressing internal crises from the point of view of the communicators in terms of the continuity of publishing and broadcasting of these crises. Furthermore, there is a lack of specific and clear local media policies to address internal crises that may occur or arise unexpectedly in society. Research recommendations: The most notable recommendations of the research include: Attention must be paid to the development of strategies and mechanisms to deal with internal crises in local media. Attention must be paid to problems and issues that may result in internal crises through their dissemination and publication in the local media.